Perubahan Kadar MDA, SOD, dan Kapasitas Antioksidan Hati Tikus sprague dawley pada Pemberian Ekstrak Bubuk Daun Cemcem (spondias pinnata (l.f) kurz) - Sulistyadewi, Ni Putu Eny; Wrasiati, Luh Putu; Wartini, Ni Made (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2015)
Cemcem leaves (Spondias pinnata (Lf) kurz is one plant that is used as a traditional drink for health benefits. This study was carried out to (1) Influence of Cemcem leaves powder extract to increased antioxidant capacity, enzyme activity of Superoxide Dismutase (SOD) and Malondialdehyde (MDA) levels in the Sprague Dawley (SD) rat liver and (2) determine the best doses to increased antioxidant capacity and enzym activity of SOD and decreas the levels of MDA in the Sprague Dawley (SD) rat liver. Methods used to determination of the effect of Cemcem leaves powder extract on levels of antioxidant capacity, SOD and MDA were performed in SD rat. The dose which was consumed were 50 mg/kg/day, 100 mg/kg/day, 150 mg/kg/day, and 200 mg/kg/day. The results showed that the cemcem leaves powder extract that was consumed orally for seven weeks at a dose of 50 mg / kg / day up to 200 mg / kg / day was able to significantly (P <0.05) decrease the levels of MDA and increase antioxidant capacity and SOD enzyme activity in rat liver. The conclusion of this study is that the extract at a dose of 50 mg / kg / day up to 200 mg / kg bw / day can increase the antioxidant capacity and SOD enzyme activity, as well as decrease the levels of MDA in the Sprague Dawley rat liver and Cemcem leaves powder extract at a dose of 200 mg / kg / day have the same ability by administering Vitamin C 50 mg / kg / day. Keywords : Cemcem Leaf Powder Extract, Maltodextrin, antioxidant capacity, SODand MDA